Evaluating the Mechanical Performance Properties of Reclaimed Asphalt Pavement Rejuvenated with Different Rejuvenators - Hasan H Joni; Rasha H A Al-Rubaee; Mohammed Kh. Shames (Wasit Journal of Engineering Sciences)
The importance of sustainability in road construction using and renewing the Reclaimed Asphalt Pavement (RAP) resulting from the reconstruction or periodic maintenance of roads is a challenge that requires the use of regenerative additions to restore the characteristics of the old bitumen in pure rap, in order to improve the performance properties of these renewable mixers. As there are many promising studies in this regard. The objective of this study is to recycle and restore RAP using two types of renovators; Waste Cooking Oil (WCO) and Asphalt Cement (AC (85-100)). Five percentages (1, 1.5, 2, 2.5 and 3) % by weight of both types of renovators were added to the RAP, separately, for the purpose of rejuvenation. Marshall Test was performed on the renovated samples to obtain the optimum percentages, which will be adopted in subsequent tests, which include; indirect tensile strength (ITS), tensile strength Ratio (TSR) and Duple Punch Shear Strength Test (DPSST) to evaluate the performance of rejuvenated RAP mixes and compare them with the original RAP. The outcomes indicated that (1.5 and 2.5) % are the optimal percentages for (WCO and AC (85-100)), respectively. In addition, the results of the performance tests indicated that the renovated RAP mixes are better than the original RAP in terms of stability, temperature susceptibility, stripping resistance and resistance to moisture damage, as well as achieving the specification requirements for the surface course. This indicates that the recycling process is of economic, environmental benefit and industrial sustainability.